(3-i)+(22+4i)

I^31=?

3+4i / 16-2i

please HELP!

Tutors, sign in to answer this question.

Robert S. | Robert Math PhysicsRobert Math Physics

(3-i)+(22+4i) combine like terms

(3+22)+(4i-i) = 25 + 3i

last term

3 + 4i / 16 -2i this needs to be in the form x + iy therefore the i needs to be taken out of the denominator

to do this requires that 16 - 2i be multiplyed by its complex congregate which is 16 + 2i but that also must be multiplied in the numerator

in the denominator 16 -2i x 16 + 2i = 16x16=256 -2i x 2i = -4 x -1 =4 for the mildde term it is -32i +32i = 0

so the denominator becomes 260

since the numerator must also be multiplied by 16 + 2i now the numerator is 3+4i x 16 + 2i

3x16=48 4i x 2i = 8 x -1 = -8 the middle term is 64i + 6i = 70i

in the numerator collecting terms is 40 + 70i and the denominator is 260

40 + 70i / 260 = 40/260 + 70i/260

1.

( 3 - i ) + ( 22 + 4i ) = (3 + 22) + (-1 + 4) i = 25 + 3i

2.

2.

i^31 = ?

i := √(-1) where := means "is defined as"

i^0 =1 because i^0 = i^(1-1) = i/i = 1

i^1 = i

i^2 = -1 because (√(a))^2 = a

i^3 = -i

i^4 = 1 because -i(i) = -i^2 = -(-1) = 1

and if you keep going you will see that the values of powers of i cycle through the four numbers 1, i, -1, -i.

So i^x = i^(remainder(x/4)), and

i^31 = i^3 = -i

3.

(3+4i) / (16-2i) =

(3+4i) / (2(8-i)) =

((3+4i) / (2(8-i)))*((8+i)/(8+i)) =

(3+4i)(8+i) / (2(8-i)(8+i)) =

(24 + 3i + 32i +4i^2) / (2(64 + 8i - 8i - i^2)) =

(24 + 35i - 4) / (2(64 + 1)) =

(20 + 35i) / (2(65)) =

(20 + 35i) / 130 =

20/130 + (35/130) i =

2/13 + (7/26) i

Parviz F. | Mathematics professor at Community CollegesMathematics professor at Community Colle...

i ^31 = (i ^4) ^7 . i^3 = -i

( 3 - i ) + ( 22 +4i) = 25+ 3i

( 3 +4i) * (16 + 2i) =

16 - 2i 16 + 2i

48 +64i +6i -8 = 40 + 70 i

256 +4 260 260

= 2 + 7 i

13 26

Exponents of i

i^2 = -1

i ^3 = i^2 . i = -i

i^4 = (i^2) ^2 = ( -1) ^2 = 1

For numbers n > 4

i^n = i ^ (4n + 1 ) = i ^ 4n . i = i

i ^ ( 4n + 2 ) = i ^4n . i^2 = -1

i ^ ( 4n + 3 )= i ^4n . i ^3 = - i

(3-i)+(22+4i)= 3-i+22+4i

In this case, treat i like a variable and just combine like terms= 25+3i

i^31

i^2 = -1, so i^31= i^30 x i^1

i^30= -1x15= -15

i^30 x i^1= -15i

3+4i/16-2i = (3+4i)(16+2i)/(16-2i)(16+2i)

(3+4i)(16+2i) = 48+6i+24i+8(i)^2

(16-2i)(16+2i) = 256-4(i)^2

48+30i+8(-1) / 256-4(-1)

48+30i-8/256+4

48+30i-8/260

56+30i/260

divide the whole equation by 2 = 28+15i/130

Already have an account? Log in

By signing up, I agree to Wyzant’s terms of use and privacy policy.

Or

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Your Facebook email address is associated with a Wyzant tutor account. Please use a different email address to create a new student account.

Good news! It looks like you already have an account registered with the email address **you provided**.

It looks like this is your first time here. Welcome!

To present the tutors that are the best fit for you, we’ll need your ZIP code.

Please try again, our system had a problem processing your request.

## Comments